CONCEPTUALISATION OF DEATH AND RESURRECTION IN THE HOLY QURAN:A COGNITIVE-SEMANTIC APPROACH - Sardaraz, Khan; Roslan, Ali (Universiti Sultan Zainal Abidin, 2016)
Conceptual metaphor is the discursive linguistic strategy employed in the Holy Quran to imprint upon the human mind the Quranic worldview. This approach can better explain the abstract concepts of death and resurrection in the Holy Quran through cross domain mapping with human experiential concepts. Traditional exegetes and rhetoricians missed this phenomenon in the Holy Quran because of their preoccupation with rhetorical and theological aspects of death and resurrection. The existing cognitive semantic research has also paid little or no attention to the investigation of death and resurrection in the Holy Quran. Therefore, this paper attempts to investigate the conceptual metaphor themes of death and resurrection in the Holy Quran. Data were retrieved from the Holy Quran on the basis of key words and phrases encapsulating the abstract concepts of death and resurrection. The analysis of data reveals various conceptual metaphor themes. It is also found that the data question the asymmetrical hypothesis of conceptual metaphor theory and its role as a sole model of metaphor interpretation. This study is part of the growing research on conceptual metaphor in the Holy Quran and is hoped to contribute to further research on the cognitive semantic analysis of the Holy Quran